2019
DOI: 10.1007/s00018-019-03279-y
|View full text |Cite
|
Sign up to set email alerts
|

Copper-mediated thiol potentiation and mutagenesis-guided modeling suggest a highly conserved copper-binding motif in human OR2M3

Abstract: Sulfur-containing compounds within a physiological relevant, natural odor space, such as the key food odorants, typically constitute the group of volatiles with the lowest odor thresholds. The observation that certain metals, such as copper, potentiate the smell of sulfur-containing, metal-coordinating odorants led to the hypothesis that their cognate receptors are metalloproteins. However, experimental evidence is sparse-so far, only one human odorant receptor, OR2T11, and a few mouse receptors, have been rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 121 publications
2
18
0
Order By: Relevance
“…Hence, strategies aiming at enhancing the sampling of the conformational space of the receptor-ligand complex have been applied to overcome this limitation. These include flexible docking approaches and experimental data-driven model refinement (Di Pizio et al 2017 ; Nowak et al 2018 ; Bushdid et al 2018 ; Bushdid et al 2019 ; Di Pizio et al 2020a , b ), as well as molecular dynamics (MD) simulations (Gelis et al 2012 ; Charlier et al 2012 ; Charlier et al 2013 ; Topin et al 2014 ; Marchiori et al 2013 ; Sandal et al 2015 ; Li et al 2016 ; Fierro et al 2017 ; Ahmed et al 2018 ; Fierro et al 2019 ; Alfonso-Prieto et al 2019a , 2019b ; Haag et al, 2020 ; Schneider et al 2020 ).…”
Section: Computational Structural Methodsmentioning
confidence: 99%
“…Hence, strategies aiming at enhancing the sampling of the conformational space of the receptor-ligand complex have been applied to overcome this limitation. These include flexible docking approaches and experimental data-driven model refinement (Di Pizio et al 2017 ; Nowak et al 2018 ; Bushdid et al 2018 ; Bushdid et al 2019 ; Di Pizio et al 2020a , b ), as well as molecular dynamics (MD) simulations (Gelis et al 2012 ; Charlier et al 2012 ; Charlier et al 2013 ; Topin et al 2014 ; Marchiori et al 2013 ; Sandal et al 2015 ; Li et al 2016 ; Fierro et al 2017 ; Ahmed et al 2018 ; Fierro et al 2019 ; Alfonso-Prieto et al 2019a , 2019b ; Haag et al, 2020 ; Schneider et al 2020 ).…”
Section: Computational Structural Methodsmentioning
confidence: 99%
“…These factors regulate the expression of several dozens of genes, including genes for which the products take part in the reprogramming of energy metabolism in tumor cells. Moreover, copper is required for the induction of Golgi-complex-independent secretion of interleukins and cytokines [ 61 ] as well as for odorant receptor activation [ 62 ]. It has also been shown that copper controls organogenesis and cell differentiation in embryo development [ 63 ].…”
Section: The Biological Roles Of Copper and Its Turnover In The Mammalian Bodymentioning
confidence: 99%
“…Thus, IAV RNA-transcriptase activity is inhibited by copper chelators in vitro and in vivo [ 174 ]. Additionally, IAV, similar to SARS-CoV-2, causes loss of smell [ 175 , 176 ], and the co-activators of the odorant receptors are copper ions [ 62 ]. Moreover, IAV uses cell-signaling cascades for its reproduction, including copper-dependent signaling pathways [ 177 , 178 ].…”
Section: The Points In Which Iav-induced Inflammation Cross With Copper Metabolismmentioning
confidence: 99%
“…C-terminal numbering starts after Y7.53. 59 Moreover, the specific constitution of these motifs is class-specific, for example, the dominant "[+]x[+]" motif at C-term 3-5 , which occurs at high rates in either class, is predominantly a "KxK" in class-I ORs, but a "RxK" or "RxR" in class-II ORs, and has been shown previously to be highly conserved within ORs. 31,40,41 As the variables plot in Figure 1 shows, the major contributors to the differentiation of class-I and class-II ORs are the class-I-specific "[+] x[+]" motif at C-term 8-10 , and the class-II-specific "[+][+]" motif at C-term 12-13 (Figure 1A).…”
Section: Conserved C-terminal Short Amino Acid Motifs In Ors Discriminate Between Class-i and Class-ii Receptorsmentioning
confidence: 99%